Reforms, Incentives and Banking Sector Productivity: A Case of Nepal - Kul B. Luintel; Sheikh Selim; Pushkar Bajracharya (Cardiff University, Cardiff Business School, 2014)
We model banks as profit-cum-utility maximizing firms and study, inter alia, bankers' incentives (optimal effort) and incentive driven productivity following deregulations. Our model puts to test a panel of Nepalese commercial banks which went through deep financial reforms in the recent past. We find that (i) bankers' efforts and productivity have notably improved in Nepal, (ii) bankers' efforts significantly explain the banking sector's productivity, (iii) the proportion of non-performing loans has considerably declined, and (iv) banking services have become costly, although the bank spread has moderately declined. Our approach is different from the widely used data envelopment analysis (DEA) of bank productivity, hence complements the literature. It also informs the current policy debate in Nepal where the Central Bank is seen to be geared towards regulating the financial system and micro-managing the banking institutions.
Keywords: G21; G28; O43; O53; 330; Reforms; incentives; productivity; panel integration; cointegration; simulation